Gold Nanoparticle Inhibits the Tumor-Associated Macrophage M2 Polarization by Inhibiting m6A Methylation-Dependent ATG5/Autophagy in Prostate Cancer - Yuanyuan Hao; Feng Duan; Xianning Dong; Ran Bi; Yinzhe Wang; Senqiang Zhu; Jinghai Hu (Analytical Cellular Pathology)
Conclusion: The ATG5/autophagy pathway is inhibited by AuNP treatment in an METTL3/m6A-dependent manner. AuNPs inhibit the TAM M2 polarization in HSPC and CRPC by inhibiting ATG5/autophagy.